New frames of Besov and Triebel-Lizorkin spaces - Dachun Yang (Journal of Function Spaces and Applications)
Let s≺0. The author obtains some new frames for Besov spaces Bpqs(ℝn) with 1≤p, q≤∞ and Triebel-Lizorkin spaces Fpqs(ℝn) with 1≺p≺∞ and 1≺q≤∞ by a dual method via the subatomic characterizations of these spaces when s≻0.